The Cervical Cancer Prevention And Care Cascade For Women Living With Hiv In Sub-Saharan Africa: Delphi Consensus Process By Dr Maša Davidović, Graduate School For Health Sciences (Ghs) University Of Bern And Swiss Tropical And Public Health Institute (Swiss Tph) - Davidović, Maša (My University, 2023)
The project has aim to develop internationally agreed-upon indicators to monitor provision of cervical cancer care to women living with HIV in sub-Saharan Africa throughout consensus process with stakeholders from this region.
Keywords: sub-Sahran Africa; cervical cancer screening; cancer cascade